The Synergistic Effects of 5-Aminosalicylic Acid and Vorinostat in the Treatment of Ulcerative Colitis - He, Long; Wen, Shuting; Zhong, Zhuotai; Weng, Senhui; Jiang, Qilong; Mi, Hong; Liu, Fengbin (Frontiers in Pharmacology, 2021)
5-aminosalicylic acid (5-ASA) drugs are the first-line therapy for the treatment of ulcerative colitis (UC) from mild to moderate. However, in some cases, 5-ASA can’t achieve desired therapeutic effects. Therefore, patients have to undergo therapies including immunosuppressants, corticosteroids or monoclonal antibodies, which are expensive and may be accompanied with significant side effects. Synergistic drugs combinations can achieve greater therapeutic effects than single drug while contribute to combating drug resistance and lessen toxic side effects. Thus, in this study, we sought to identify synergistic drugs for 5-ASA. Based on network of protein-metabolite analysis, and integrate KEGG pathway enrichment analysis, pathway-pathway interaction analysis, and semantic similarity analysis, we identified vorinostat (SAHA) can work synergistically with 5-ASA by their synergistic inhibition of NF-kB signaling pathway in the treatment of ulcerative colitis. Moreover, their synergistic effects may also be associated with metabolite-butyric acid. Therefore, we determined that SAHA can act synergistically with 5-ASA in the treatment of ulcerative colitis and validated their synergistic effects by experiments both in vitro and in vivo.